The Implementation of Therapeutic Communication in the Orientation Phase on Family Satisfaction of Patients Treated in the Intensive Care Unit (ICU) at Ibnu Sina Regional General Hospital, Gresik - Evriliatul Atalla Nafis Putri Andriani (Global Ten Public Health and Nursing Journal, 2025)
Intensive Care Unit (ICU) services often cause anxiety among families due to patients’ critical conditions and limited access to information. The orientation phase of therapeutic communication plays an essential role in enhancing clarity, safety, and trust. This study aimed to analyze the effect of implementing therapeutic communication in the orientation phase on family satisfaction of patients treated in the ICU of Ibnu Sina Gresik Hospital. This study used a pre-experimental one-group pretest–posttest design without a control group. The population consisted of all family members waiting in the ICU, and 30 respondents were selected through purposive sampling based on inclusion criteria. The independent variable was the implementation of the orientation phase of therapeutic communication, while the dependent variable was family satisfaction. Data were obtained using a validated and reliable family satisfaction questionnaire. The intervention consisted of a structured orientation phase conducted by nurses, including self-introduction, role explanation, time contracting, initial information provision, orientation to ICU procedures and environment, and opportunities for clarification. Data collection was carried out in two stages: pretest before the intervention and posttest after the intervention. Data analysis included univariate distribution and Wilcoxon Signed Rank Test to measure changes in satisfaction. Results indicated a significant improvement in family satisfaction after the intervention (p=0.000; p<0.05). Most respondents reported moderate satisfaction before the intervention and shifted to satisfied to very satisfied afterward. It is concluded that systematic implementation of the orientation phase of therapeutic communication effectively increases family satisfaction in the ICU.